2020
DOI: 10.3847/1538-4357/ab65ed
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Calibration of the Reddening Maps in the Magellanic Clouds

Abstract: We present reddening maps of the Large Magellanic Cloud (LMC) and Small Magellanic Cloud (SMC), based on color measurements of the red clump. Reddening values of our maps were obtained by calculating the difference of the observed and intrinsic color of the red clump in both galaxies. To obtain the intrinsic color of the red clump, we used reddenings obtained from late-type eclipsing binary systems, measurements for blue supergiants and reddenings derived from Strömgren photometry of B-type stars. We obtained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 46 publications
10
65
2
2
Order By: Relevance
“…These authors found similar results as Haschke et al (2011) and Subramanian & Subramaniam (2012). Very recently Górski et al (2020) produced revised reddening maps which show similar spatial variations of the reddening as Haschke et al (2011), but their values are systematically higher.…”
Section: Nir Metallicity Maps Of the Smcsupporting
confidence: 52%
“…These authors found similar results as Haschke et al (2011) and Subramanian & Subramaniam (2012). Very recently Górski et al (2020) produced revised reddening maps which show similar spatial variations of the reddening as Haschke et al (2011), but their values are systematically higher.…”
Section: Nir Metallicity Maps Of the Smcsupporting
confidence: 52%
“…Another technique for estimating the extinction is based on the OGLE reddening maps [31] using Red Clump stars as tracers and RR Lyrae stars in the LMC, leading to intermediate adopted values [17,21,32]…”
Section: B Large Magellanic Cloudmentioning
confidence: 99%
“…The widely used reddening maps of Haschke et al (2011) adopted a theoretical value of 0.92 mag and 0.89 mag for (V−I) 0 in the center of the LMC and SMC, respectively. Górski et al (2020) measured (V−I) 0 =0.838 mag for the LMC and (V−I) 0 =0.814 mag for the SMC, which are a mean of four distinct methods. Nataf et al (2020) employed a hybrid theoretical and empirical approach and derived (V−I) 0 ={0.89, 0.92, 0.88} mag for the LMC, using three different methods, and (V−I) 0 ={0.84, 0.84} mag for the SMC.…”
Section: Determining the (V−i) 0 Of The Red Clumpmentioning
confidence: 90%
“…We also provide ±34.1% percentile values from the median as a measure of confidence intervals and of differential reddening. Previous studies of reddening in the Magellanic Clouds typically used a combination of a Gaussian and a polynomial to fit the RC distribution (e.g., Haschke et al 2011;Choi et al 2018;Górski et al 2020). However, this has a tendency to miss the RGB contamination entirely and focus the polynomial on the smooth stellar background instead.…”
Section: Determining the Red Clump Colormentioning
confidence: 99%
See 1 more Smart Citation